Дослідження сучасних уявлень про природу формування відкладень в вогнетривах при розливаннi сталі. Повідомлення 1 - Писарський, С.М.; Смірнов, О.М. (Physico-technological Institute of Metals and Alloys, 2023)
When studying the phenomenon of clogging, a theoretical analysis of its physicochemical nature and regularities, along with the search for countermeasures, was always considered as a priority. However, a number of fundamental issues related to this phenomenon, still continues to be the subject of scientific discussions. The performed analytical study of currently known ideas about the mechanisms (models) of the deposit formation showed: the lack of complete clarity in understanding the role of a number of factors; lack of detail on a number of important aspects of the phenomenon under consideration; discrepancy of some basic ideas on the processes accompanying the formation of deposits, to the known thesis of physics and chemistry. Based on the thermodynamic analysis of the process of adsorption of surface-active oxygen in iron, it has been shown that the idea of intensive movement of inclusions in the gradient (diffusion) fields of oxygen concentration at the “metal-refractory (deposit)” interface in majority of the possible cases is incorrect. In the course of a comparative morphological analysis of inclusions present in steel and deposits, it was shown that the similarity of terminology in the definition of morphological types for them does not mean their identity. Differences in the morphology and chemical composition of the compared inclusions indicate that the formation of deposits is not always associated with the precipitation onto the surface of refractories of deoxidation products present in the steel. Basing on the results of analytical studies it was preliminary concluded, that it is necessary to develop, in addition to the existing one new model of this phenomenon. Differing in its universalism, it should extend to refractories of any composition and to all stages of the deposit formation.